PENGARUH INSENTIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. KAI UNIT PELAKSANA TEKNIS MALANG - Mahfud Tono Tiyanto; Rofikul Amin (Jurnal Manajemen dan Kewirausahaan, 2016)
This research analizes about the affect of incentives and discipline factors on the employees performance The respondents of this study are employees of PT. KAI Technical Implementation Unit Malang. The results of this study shows a positive and significant affect of incentives and labor discipline on the employees performance. Discipline is the dominant factor that influence on employee performance.